(untitled) (Research, Society and Development, 2021)
The pandemic caused by the new coronavirus has increased the exposure of children and adolescentes to the risks of domestic accidents; however, it has also enabled a greater contact with digital technologies for educational purposes and/or entertainment. This work was intended to introduce a literature review and the exploration of reality for the preparation of a technology in self-care in the prevention of domestic accidents, with a focus on elementary school children. This is a methodological study focused on preliminary results for the definition of the theoretical framework and the educational technology to be adopted. A literature review was conducted by searching for manuals and recommendations, as well as scientific articles, which addressed the construction and validation of educational technologies on the topic. For the reality exploration stage, it was decided to carry out an educational intervention with the theme “Domestic Accidents”, applying a questionnaire with 120 students enrolled in fourth and fifth grade classes of elementary school, during the period from March to June 2019. The questionnaire featured illustrations and consisted of 9 objective questions. The literature review showed that there is a scarcity of educational technologies applied for this purpose and directed to this age group, while the exploratory reality research showed that a large portion of the participants were affected by domestic accidents, such as cuts and burns, and that a large portion used inappropriate care. Conducting a literature review and getting to know the reality associated with the experiences of the researchers are fundamental steps and contribute to the development of an educational technology that meets the real needs of the target audience.